ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) AMANAH MANDIRI KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI PEKANBARU - Astari, Khairani; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Economic Business of the Saving Loan (UEK-SP) plays a very important role in supporting the economic growth and development of the community at the village level. Therefore, a good UEK SP processing is needed in order to survive and continue to serve the needs of the community. As a village-owned enterprise, UEK SP has relatively smaller capital than other financial institutions, such as cooperatives. So it is necessary to process working capital that is very efficient and effective to achieve maximum profitability. The purpose of this study is to determine the management of working capital in increasing profitability and the policies carried out at the Economic Business of the Savings and Loans (UEK-SP) Amanah Mandiri, East Sidomulyo Village, Marpoyan Damai District, Pekanbaru. This study uses descriptive analysis by analyzing financial ratios such as working capital turnover ratios and profitability ratios. The results showed that the management of working capital in the sub-district economic enterprises (UEK) was better than the savings and loan unit. It caused the limited working capital in the savings and loan business unit requires, so the village government must to increase the working capital owned by the savings and loan unit, for example by setting aside profits from UEK to increase the working capital of the savings and loan unit. Therefore, the savings and loan unit can increase its profitability. Keywords: Working Capital, Profitability, Economic Enterprises Savings and Loans Village